Correction: Unravelling the impact of hydrocarbon structure on the fumarate addition mechanism – a gas-phase ab initio study. Issue 14 (22nd March 2018) - Bharadwaj, Vivek S.; Vyas, Shubham; Villano, Stephanie M.; Maupin, C. Mark; Dean, Anthony M.
Abstract : Correction for 'Unravelling the impact of hydrocarbon structure on the fumarate addition mechanism – a gas-phase ab initio study' by Vivek S. Bharadwaj et al., Phys. Chem. Chem. Phys., 2015, 17, 4054–4066.